Gratitude as a predictor of resilience - Wustari Mangundjaya; Almira Nurul Rezeki (Sean Institute, 2024)
The COVID-19 pandemic has brought various impacts. Some companies are experiencing economic downturns, so they lay off their employees. This is affected by employees who have been laid off so during the COVID-19 pandemic, attitudes and behaviors are needed in individuals always to be grateful and able to bounce back. The aim is to reveal the relationship between gratitude and resilience for employees affected by layoffs, namely men who work, and how to calm the minds of victims of layoffs. This study used quantitative methods with a correlational approach. Data was collected with 2 types of questionnaires, namely gratitude and resilience. 99 respondents in the South Tambun region face layoffs at their companies due to the economic crisis. The results showed that gratitude as a predictor on resilience. With this result, it can be said to develop resilience can be done by developing gratitude